Widespread reduction in sun-induced fluorescence from the Amazon during the 2015/2016 El Niño. (8th October 2018) - Koren, Gerbrand; van Schaik, Erik; Araújo, Alessandro C.; Boersma, K. Folkert; Gärtner, Antje; Killaars, Lars; Kooreman, Maurits L.; Kruijt, Bart; van der Laan-Luijkx, Ingrid T.; von Randow, Celso; Smith, Naomi E.; Peters, Wouter
Abstract : The tropical carbon balance dominates year-to-year variations in the CO2 exchange with the atmosphere through photosynthesis, respiration and fires. Because of its high correlation with gross primary productivity (GPP), observations of sun-induced fluorescence (SIF) are of great interest. We developed a new remotely sensed SIF product with improved signal-to-noise in the tropics, and use it here to quantify the impact of the 2015/2016 El Niño Amazon drought. We find that SIF was strongly suppressed over areas with anomalously high temperatures and decreased levels of water in the soil. SIF went below its climatological range starting from the end of the 2015 dry season (October) and returned to normal levels by February 2016 when atmospheric conditions returned to normal, but well before the end of anomalously low precipitation that persisted through June 2016. Impacts were not uniform across the Amazon basin, with the eastern part experiencing much larger (10–15%) SIF reductions than the western part of the basin (2–5%). We estimate the integrated loss of GPP relative to eight previous years to be 0.34–0.48 PgC in the three-month period October–November–December 2015. This article is part of a discussion meeting issue 'The impact of the 2015/2016 El Niño on the terrestrial tropical carbon cycle: patterns, mechanisms and implications'.